XVII-wieczne medale oraz numizmaty pamiątkowe poświęcone oblężeniu osmańskiemu Wiednia w 1683 roku i jego niektórym aspektom - Rokita, Jan Gustaw (Studia Europaea Gnesnensia, 2019)
The chief aim of the paper is to introduce the reader to five specific pieces of medallic art, answer the questions what propaganda goals they were to accomplish, as well as provide am iconographic analysis, in comparison with selected examples of medals, graphic works, sculptures, and handicrafts.